The Society of Remote Control: AI and Other Intelligences - Jeremy Tambling (Anglica. An International Journal of English Studies)
The paper reads the power of social media, especially Artificial Intelligence, in the light of Foucault, and Benjamin, and, especially, Deleuze, on the society of control, as he calls it: to which this paper adds the word “remote” since this quality is even more pertinent to the present-day than Foucault’s idea of the classical Panopticon. It examines different senses of the word “intelligence,” drawing on Catherine Malabou to underscore the idea of the brain’s “plasticity,” something ignored when the brain, and its contents, and communication, are treated as so much “data.” It concludes by asking what role AI might have in the humanities.